Current Status of Mechanical Circulatory Support: A Systematic Review - Kyriakos Spiliopoulos; Gregory Giamouzis; George Karayannis; Dimos Karangelis; Stelios Koutsias; Andreas Kalogeropoulos; Vasiliki Georgiopoulou; John Skoularigis; Javed Butler; Filippos Triposkiadis (Cardiology Research and Practice)
Heart failure is a major public health problem and its management requires a significant amount of health care resources. Even with administration of the best available medical treatment, the mortality associated with the disease remains high. As therapeutical strategies for heart failure have been refined, the number of patients suffering from the disease has expanded dramatically. Although heart transplantation still represents the gold standard therapeutical approach, the implantation of mechanical circulatory support devices (MCSDs) evolved to a well-established management for this disease. The limited applicability of heart transplantation caused by a shortage of donor organs and the concurrent expand of the patient population with end-stage heart failure led to a considerable utilization of MCSDs. This paper outlines the current status of mechanical circulatory support.